miRNAs Alter T Helper 17 Cell Fate in the Pathogenesis of Autoimmune Diseases - Huang, Junxia; Xu, Xinzhi; Yang, Ji (Frontiers in Immunology, 2021)
T helper 17 (Th17) cells are characterized by secretion of the IL-17 cytokine and are essential for immune response against bacterial and fungal infections. Despite the beneficial roles of Th17 cells, unrestrained IL-17 production can contribute to immunopathology and inflammatory autoimmune diseases, including multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease. Although these diverse outcomes are directed by activation of Th17 cells, the regulation of Th17 cells is incompletely understood. The discovery that microRNAs (miRNAs) are involved in the regulation of Th17 cell differentiation and function have greatly improved our understanding of Th17 cells in immune response and disease. Here, we provide an overview of the biogenesis and function of miRNA and summarize the role of miRNAs in Th17 cell differentiation and function. Finally, we focus on recent advances in miRNA-mediated dysregulation of Th17 cell fate in autoimmune disease.